Immobilization of cadmium in simulated contaminated soils using thermal-activated serpentine. Issue 3 (3rd May 2020) - Cao, Chun-Yan; Yu, Bing; Wang, Min; Zhao, Ying-Ying; Wan, Xin; Zhao, Shuang
ABSTRACT: The thermal-activated serpentine prepared by heating natural serpentine at different temperatures was used to immobilize cadmium (Cd) in simulated contaminated soils. The results showed that the increasing soil pH induced by adding serpentine was primarily responsible for reducing the content of TCLP-Cd (toxicity characteristic leaching procedure-Cd) in soil. Furthermore, adding thermal-activated serpentine could promote the transformation from exchangeable form of Cd in soil to low bioavailable Cd (Fe-Mn oxides, carbonate, and residual form) by surface adsorption and surface precipitation, and then reduced the bioavailability of Cd in soil. Under the same treatment condition, adding S700 (serpentine activated at 700°C) exhibited better performance to immobilization of Cd, and it could reduce exchangeable Cd by 23.76 36.49%, and increase carbonate, Fe-Mn oxide, and residual form of Cd by 6.03 8.03%, 6.05 8.35%, and 11.17 19.58%, respectively. These results indicated that thermal-activated serpentine would be the great potential for immobilization of Cd in soil.